Role of RNF20 in cancer development and progression – a comprehensive review - Sethi, G.; Shanmugam, M.; Arfuso, Frank; Kumar, Alan Prem (Portland Press Ltd., 2018)
© 2018 The Author(s). Evolving strategies to counter cancer initiation and progression rely on the identification of novel therapeutic targets that exploit the aberrant genetic changes driving oncogenesis. Several chromatin associated enzymes have been shown to influence post-translational modification (PTM) in DNA, histones, and non-histone proteins. Any deregulation of this core group of enzymes often leads to cancer development. Ubiquitylation of histone H2B in mammalian cells was identified over three decades ago. An exciting really interesting new gene (RING) family of E3 ubiquitin ligases, known as RNF20 and RNF40, monoubiquitinates histone H2A at K119 or H2B at K120, is known to function in transcriptional elongation, DNA double-strand break (DSB) repair processes, maintenance of chromatin differentiation, and exerting tumor suppressor activity. RNF20 is somatically altered in breast, lung, prostate cancer, clear cell renal cell carcinoma (ccRCC), and mixed lineage leukemia, and its reduced expression is a key factor in initiating genome instability; and it also functions as one of the significant driving factors of oncogenesis. Loss of RNF20/40 and H2B monoubiquitination (H2Bub1) is found in several cancers and is linked to an aggressive phenotype, and is also an indicator of poor prognosis. In this review, we summarized the current knowledge of RNF20 in chronic inflammation-driven cancers, DNA DSBs, and apoptosis, and its impact on chromatin structure beyond the single nucleosome level.